Ethical data acquisition for LLMs and AI algorithms in healthcare - Marta Williams; Wasie Karim; Justin Gelman; Marium Raza (npj Digital Medicine)
Abstract Artificial intelligence (AI) algorithms will become increasingly integrated into our healthcare systems in the coming decades. These algorithms require large volumes of data for development and fine-tuning. Patient data is typically acquired for AI algorithms through an opt-out system in the United States, while others support an opt-in model. We argue that ethical principles around autonomy, patient ownership of data, and privacy should be prioritized in the data acquisition paradigm.